The nutritional status of hospitalized children: Has this subject been overlooked? - Kapçı, Nermin; Akçam, Mustafa; Koca, Tuğba; Dereci, Selim; Kapcı, Mücahit (Turkish Journal of Gastroenterology, 2015)
Abstract Background/Aims: To determine the nutritional status of hospitalized children at the time of admission and to investigate the relationship between diagnosis and nutritional status. Materials and Methods: Body weight, height, triceps skinfold thickness, and mid-arm circumference were measured on admission and percentages of weight-for-age, weight-for-height, body mass index, mid-arm circumference, and triceps skinfold thickness were calculated. The nutritional status was evaluated using the Waterlow, Gomez, and other anthropometric assessments. Results: A total of 511 patients were included in the study with a mean age of 5.8±4.9 years. Malnutrition was determined in 52.7% of patients according to the Waterlow classification. Mild malnutrition was determined in 39%, moderate in 12%, and severe in 1.7%, with the characteristics of acute malnutrition in 23.9%, acute-chronic in 7.3%, and chronic in 21.5%. The highest rate of malnutrition was in the 0–2 years age group (62.3%). According to the Gomez classification, malnutrition rate was determined as 46.8%. The rates of malnutrition in malignant, gastrointestinal, and infectious diseases were 60%, 59.8%, and 54.5%, respectively. Conclusion: The prevalence of malnutrition in hospitalized children was noticeably high. The nutritional evaluation of all patients and an early start to nutritional support could provide a significant positive contribution.